Elevated dimethylarginine, ATP, cytokines, metabolic remodeling involving tryptophan metabolism and potential microglial inflammation characterize primary open angle glaucoma - Sujith Kumar Pulukool (Nature Portfolio, 2021)
Abstract Glaucoma of which primary open angle glaucoma (POAG) constitutes 75%, is the second leading cause of blindness. Elevated intra ocular pressure and Nitric oxide synthase (NOS) dysfunction are hallmarks of POAG. We analyzed clinical data, cytokine profile, ATP level, metabolomics and GEO datasets to identify features unique to POAG. N9 microglial cells are used to gain mechanistic insights. Our POAG cohort showed elevated ATP in aqueous humor and cytokines in plasma. Metabolomic analysis showed changes in 21 metabolites including Dimethylarginine (DMAG) and activation of tryptophan metabolism in POAG. Analysis of GEO data sets and previously published proteomic data sets bins genes into signaling and metabolic pathways. Pathways from reanalyzed metabolomic data from literature significantly overlapped with those from our POAG data. DMAG modulated purinergic signaling, ATP secretion and cytokine expression were inhibited by N-Ethylmaleimide, NO donors, BAPTA and purinergic receptor inhibitors. ATP induced elevated intracellular calcium level and cytokines expression were inhibited by BAPTA. Metabolomics of cell culture supernatant from ATP treated sets showed metabolic deregulation and activation of tryptophan metabolism. DMAG and ATP induced IDO1/2 and TDO2 were inhibited by N-Ethylmaleimide, sodium nitroprusside and BAPTA. Our data obtained from clinical samples and cell culture studies reveal a strong association of elevated DMAG, ATP, cytokines and activation of tryptophan metabolism with POAG. DMAG mediated ATP signaling, inflammation and metabolic remodeling in microglia might have implications in management of POAG.